2022
DOI: 10.1016/j.jfo.2021.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a full-thickness macular hole and retinal detachment secondary to toxoplasma chorioretinitis that developed shortly after COVID-19: A case report

Abstract: Bien que la toxoplasmose oculaire soit généralement une infection spontanément résolutive, elle peut entraîner une réduction sévère de l'acuité visuelle en raison d'une inflammation intense du vitré ou d'une atteinte des structures du segment postérieur. Selon la gravité de l'inflammation intraoculaire, des complications graves, notamment la membrane épirétinienne ou le décollement de la rétine, peuvent se développer. Dans cet article, nous visons à présenter un cas compliqué à la fois par un trou maculaire de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A growing number of studies have indicated that ocular manifestations can either preexist or occur as a result of SARS‐CoV‐2 infection 16,17 . Aggarwal reported that ocular manifestations were observed in 11.64% of COVID‐19‐infected patients in a meta‐analysis 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of studies have indicated that ocular manifestations can either preexist or occur as a result of SARS‐CoV‐2 infection 16,17 . Aggarwal reported that ocular manifestations were observed in 11.64% of COVID‐19‐infected patients in a meta‐analysis 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Aggarwal reported that ocular manifestations were observed in 11.64% of COVID‐19‐infected patients in a meta‐analysis 18 . Conjunctivitis appears to be the most common ocular pathology, but there is also evidence linking COVID‐19 to retinal vascular occlusions, optic neuritis and uveitis 2,16,19 . To the best of our knowledge, there have been some cases of VKH disease after COVID‐19 vaccination reported 20–22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the pathogenic examination of Toxoplasma is difficult, and the positive rate is relative low, therefore, the diagnosis of Toxoplasma is mostly based on serological examination. [ 4 ] However, serological tests alone cannot confirm the diagnosis, particularly in patients with suspected ocular Toxoplasmosis , thus, the detection of serum anti-toxoplasma antibodies can only be used as a diagnostic reference, and more importantly, the detection of Toxoplasma antibodies in intraocular fluid should be performed. Here, we reported a case with ocular toxoplasmosis diagnosed by serum and aqueous humor sample antibody tests.…”
Section: Introductionmentioning
confidence: 99%
“…directly associated with any type of RD, except in cases of secondary infections or autoimmune conditions. [4][5][6][7] There have been. However, case reports temporally link the new occurrence of RD to vaccinations against the virus.…”
mentioning
confidence: 99%